Six years of development in promoting identity formation of STEM education as a distinct field - Yeping Li (International Journal of STEM Education, 2020)
Abstract With the completion of six publication cycle years (August 2014 to July 2020), the International Journal of STEM Education has achieved important milestones in promoting the identity of STEM education as a distinct field. In this editorial, I specifically share the journal’s achievements since August 2019 and its emerging trends in leading research publications in STEM education, which reflect not only the journal’s growth with on-going strong support from researchers and readers internationally, but also the gradual formation of a broad field identity of STEM education.